Prescribed precision for medical products obtained with additive manufacturing technologies. Issue 1 (1st November 2022) - Ionescu, N; Ulmeanu, M E; Doicin, C V; Ionescu, C; Spânu, P
Abstract : The paper highlights the importance of corelating the function of a medical product, with its' design and manufacture stages within the global product design and development process. Dimensional accuracy, macro-geometric and micro-geometric shape accuracy, relative surface position accuracy and other prescribed characteristics of medical products should take into consideration a variety of factors, such as custom requirements, regulated by the product functions. In an ideal scenario, with unlimited resources, prescribed characteristics dictate the selection of the manufacturing technology and equipment. Nonetheless, in most cases the design stage takes into consideration capabilities of available technology, correlated with bespoke requirements. In this context, the authors propose a clear distinction between precision, accuracy, repeatability, and resolution, as to properly address each issue in the lifecycle of a medical product manufactured using additive technologies. Using a real application for an upper limb prosthesis, the nominal position precision is prescribed, based on size-dependent geometric tolerances, for a cylindrical surface in relation to three reference surfaces, with the application of the maximum and minimum material principles.